Kepemimpinan Camat Dalam Meningkatkan Kinerja Pegawai Di Kantor Kecamatan Muara Wahau Kabupaten Kutai Timur - Munawarah Qaullia; Adam Idris; Rita Kala Linggi (Jurnal Ilmu Pemerintahan, 2023)
This research is a descriptive qualitative research using the Miles and Huberman method, including data reduction, data presentation, and conclusion drawing. In this study the authors used observation, interview and document recording methods. Based on the results of the study, regional leaders in improving employee performance at the Muara Wahau District Office of East Kutai Regency have not been fully implemented. Decision making by the deputy regent goes well, with the participation of the apparatus so that in making decisions it is still taken into account, but only verbally, not in writing and not in the formulation of policies. In addition to flattery, the regent also pays more attention to the disbursement of compensation and salaries that should be paid because they come from the local government. Communication is also good, the deputy regent communicates in two directions and sometimes uses local language so that staff can understand and accept. However, the responsibility cannot be said to be good because of the lack of direct supervision from the deputy regent, so it is handed over to Secretary Camat and heads of departments and heads of offices despite coordination. However, when handling, regional leaders only give verbal warnings or do not impose sanctions. The inhibiting factor is the lack of responsibility of employees due to lack of understanding of using technology and frequent absences from work. Supporting factors are the availability of facilities to support work and work allowances as well as salaries as a form of appreciation.